Numerical Evaluation of Single-lap Adhesive Joints under Different Geometries and Adhesive Types - T. A. B. Fernandes; R. D. S. G. Campilho (Techniques and Innovation in Engineering Research Vol. 3, 2022)
Adhesives can be strong and brittle (e.g., Araldite® AV138) or less strong and ductile (e.g., Araldite® 2015). High strength and ductility are combined in a new family of polyurethane adhesives (like Sikaforce® 7888). In this study, the performance of the three adhesives listed above was evaluated in single-lap joints with varied overlap lengths (LO). The experimental work is complemented by a rigorous numerical study using Finite Elements, which is based on Cohesive Zone Models (CZM). This procedure enabled to check the performance of this predictive technique when applied to bonded joints. Furthermore, it was possible to determine which adhesive family is most suited for each joint geometry. CZM was shown to be highly accurate, with the exception of mainly ductile adhesives, which may be avoided by using a different cohesive law.